Opportunities of new media: semantic web - Yengin, Deniz (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2015)
Everything has a text format for individuals. These texts are being transferred to the destination with the communication process and during this transfer process channel or media is important. In this study, during communication process how the enviroment evolve with technology and this evolution's possibilities are discussed. Development of the internet is expound in the context of determinism and smart data and semantic web concept are explained with offered suggestions about the future.
Keywords: New media; internet; smart data; semantic web